Investigation of Design Parameters of Blow off Silencer for Noise Reduction in Centrifugal Compressor Application (Journal of Pharmaceutical Negative Results, 2022)
Noise is the phenomena that every living being in this earth tries to avoid. Even in engineering researchers’ works to minimize noise from machines. Similarly in case of compressors, blow off silencer is a device that requires noise attenuation. Blow-off silencer is used to reduce the noise level from the bypass line of compressor which is open to environment. In this research paper, design parameters and procedure for blow off silencer for centrifugal compressor have presented. The current available model of blow of silencer is thoroughly checked with standard procedure with numerical method. Various parameters like number of holes in diffuser, length of silencer etc. have calculated. It is found that the noise attenuation required for the silencer is 85 dB (A). The current silencer achieves noise reduction up to 96.7 dB (A). With the help of Stainless steel wool, the noise reduction is possible to 85 dB (A). Also by increasing dimensions of current silencer noise attenuation up to 85 dB (A) is possible. These various methods are discussed in this paper. Currently study is focused on designing blow off silencer for centrifugal compressor. The same method however can be implicated for other compressors as well.